Indonesian Capital Market Reaction to Jakarta’s Large Scale Social Restrictions - Catur Wicaksono, Nur Wahyu; Aryani, Y. Anni; Setiawan, Doddy (The Indonesian Capital Market Review, 2022)
This study aims to analyze the Indonesian capital market reaction to the Large-Scale Social Restrictions (PSBB) policy in Jakarta in 2020. The findings from this study can be used as a policy evaluation and as a reference to assess similar future policies to be implemented in Jakarta. Four event periods were used based on the number of times this policy was implemented in 2020. Using the event study approach and single index model method, this study used 568 companies listed on the IDX which are then divided into nine sectors. The results of this study showed that the Indonesian capital market reacted in different ways following the four periods of PSBB implementation in Jakarta. It was proven that there was no capital market reaction during the first period, a negative reaction for the second period, a positive reaction for the third period, and finally a negative reaction again for the fourth period.